Tradisi Muludan serta Implikasinya terhadap Kehidupan Sosial dan Keagamaan Perspektif Fenomenologi Edmund Husserl - Rohmat Pujiyanto; Muslihudin Muslihudin (Yumary: Jurnal Pengabdian kepada Masyarakat, 2023)
Purpose: The purpose of this study is to describe the implementation of the muludan sholawatan tradition for 12 nights in the villages of Kaliwuluh, Kebakkramat, Karanganyar and its implications for the development of social and religious life from Edmund Husserl's point of view for the people of Kaliwuluh village. Methodology/approach: This research includes qualitative field research. then using observation and interview methods in obtaining data. Next, to analyze the data using data reduction techniques. the findings of this study indicate that the muludan tradition in Kliwuluh village is carried out by increasing remembrance and prayer for 12 consecutive nights. Judging from Edmund Husserl's phenomenological concept, the 12-night muludan tradition has implications for the social and religious development of the Kaliwuluh village community. Results/findings: Social development has implications for the value of sulaturrahmi and mutual cooperation (phenomenology and phenomenological reduction), the value of togetherness (awareness and Labenswelt), and the value of caring (eiditic and transcendental reduction). Then towards religious development it has implications for the value of mahabbah or love for God, the Prophet and the scholars (intentionality), the value of alms (apoche and eiditic reduction) and the value of tholabul 'ilmi or seeking religious knowledge (labenswelt).